2022
DOI: 10.1371/journal.pone.0272836
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal painting in Charadrius collaris Vieillot, 1818 and Vanellus chilensis Molina, 1782 and an analysis of chromosomal signatures in Charadriiformes

Abstract: Charadriiformes represent one of the largest orders of birds; members of this order are diverse in morphology, behavior and reproduction, making them an excellent model for studying evolution. It is accepted that the avian putative ancestral karyotype, with 2n = 80, remains conserved for about 100 million years. So far, only a few species of Charadriiformes have been studied using molecular cytogenetics. Here, we performed chromosome painting on metphase chromosomes of two species of Charadriidae, Charadrius c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Previously, analyzing the macrochromosomes using chromosome painting, we proposed that, after divergence, each shorebird suborder underwent different chromosome rearrangements [ 13 ], which was later confirmed by others [ 12 ]. Here, we extended this hypothesis to microchromosomes as well.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Previously, analyzing the macrochromosomes using chromosome painting, we proposed that, after divergence, each shorebird suborder underwent different chromosome rearrangements [ 13 ], which was later confirmed by others [ 12 ]. Here, we extended this hypothesis to microchromosomes as well.…”
Section: Discussionmentioning
confidence: 85%
“…chilensis and C . collaris , Pinheiro et al [ 12 ] found differences in the microchromosomes with FISH signals using Burhinus oedicnemus probes corresponding to microchromosomes. These authors suggested that the variation in the number of signals was indicative of the considerable number of rearrangements involving microchromosomes in V .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations